2016
DOI: 10.1002/adfm.201604300
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer Cell Membrane-Coated Gold Nanocages with Hyperthermia-Triggered Drug Release and Homotypic Target Inhibit Growth and Metastasis of Breast Cancer

Abstract: The cell‐specific targeting drug delivery and controlled release of drug at the cancer cells are still the main challenges for anti‐breast cancer metastasis therapy. Herein, the authors first report a biomimetic drug delivery system composed of doxorubicin (DOX)‐loaded gold nanocages (AuNs) as the inner cores and 4T1 cancer cell membranes (CMVs) as the outer shells (coated surface of DOX‐incorporated AuNs (CDAuNs)). The CDAuNs, perfectly utilizing the natural cancer cell membranes with the homotypic targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
214
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(216 citation statements)
references
References 39 publications
2
214
0
Order By: Relevance
“…Unfortunately, DOX also can induce toxic and side effects in many organs. Animal experiment demonstrated it cased cardiac toxicity in 4T1 tumor‐bearing mice (H. P. Sun et al, ). In our study, the obvious accumulation of neutrophils was observed in the heart of DOX group, while there were no obvious damage signal observed in major organ including hearts from hematoxylin and eosin (H&E)‐stained slices of DOX–MNPs treated groups (Figure ; Figure S3B).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, DOX also can induce toxic and side effects in many organs. Animal experiment demonstrated it cased cardiac toxicity in 4T1 tumor‐bearing mice (H. P. Sun et al, ). In our study, the obvious accumulation of neutrophils was observed in the heart of DOX group, while there were no obvious damage signal observed in major organ including hearts from hematoxylin and eosin (H&E)‐stained slices of DOX–MNPs treated groups (Figure ; Figure S3B).…”
Section: Resultsmentioning
confidence: 99%
“…Further, polymer tethers can be used introduce elements onto the outer membrane surface that can provide additional functionality such as tumor targeting and penetration [113,216,217]. Other strategies have been developed that can enable on-demand, triggered release of cancer drugs, helping to further improve nanoparticle efficacy and minimize systemic toxicity [218221]. One major advantage of the RBC membrane coating is that it enables extended circulation after repeated administration due to its biocompatible and nonimmunogenic nature [222].…”
Section: Cell Membrane-based Nanostructuresmentioning
confidence: 99%
“…Statistical significance: * p < 0.05 and ** p < 0.01. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Homotypic Targetingmentioning
confidence: 99%
“…Recently, homotypic targeting strategy has been proposed to improve the outcomes of some combination therapy. Sun et al developed the DOX‐loaded gold nanocage as the inner core to construct 4T1 breast tumor cell membrane–coated nanomedicine to realize the homotypic targeting mediated combination therapy (Figure B) . Arising from the photothermal property of gold nanocage and hyperthermia‐triggered release of DOX, accompanied with homotypic self‐recognition of tumor cell membranes, the inhibiting rates of tumor volume and metastatic nodules of about 98.9% and 98.5% were observed in the 4T1 orthotopic mammary tumor.…”
Section: Homotypic Targetingmentioning
confidence: 99%